1992
DOI: 10.3382/ps.0710516
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Different Types of n-3 Fatty Acids Into Tissue Lipids of Poultry

Abstract: The objective of the present study was to compare the incorporation of different types of n-3 polyunsaturated fatty acids into thigh muscle lipids of poultry. Nine groups of broiler chicks were fed diets supplemented with three levels (1.0, 2.5, and 5.0%) of either corn, linseed, or menhaden oil. Birds supplemented with linseed oil, rich in linolenic acid (C18:3n-3), had significantly higher levels of n-3 fatty acids and higher n-3:n-6 ratios than those supplemented with the same level of menhaden oil, primari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 17 publications
4
18
0
1
Order By: Relevance
“…Lopez-Ferrer et al (2001) found out that increasing dietary levels of LNA resulted in an increase in the contents of EPA and DHA in TM; in our experiment, however, this observation for DHA was not corroborated. Our results support the theory that broiler chickens show a limited capacity to desaturate and elongate the chain of LNA (Chanmugam et al, 1992;Lopez-Ferrer et al, 1999).…”
Section: Resultssupporting
confidence: 80%
“…Lopez-Ferrer et al (2001) found out that increasing dietary levels of LNA resulted in an increase in the contents of EPA and DHA in TM; in our experiment, however, this observation for DHA was not corroborated. Our results support the theory that broiler chickens show a limited capacity to desaturate and elongate the chain of LNA (Chanmugam et al, 1992;Lopez-Ferrer et al, 1999).…”
Section: Resultssupporting
confidence: 80%
“…It is obvious that in the enzymatic competition between n-6 and n-3 FA families there was a lack of enzymes required for the elongation of n-6 FA family (Holman andMohrhauer, 1963, Crespo andEsteve-Garcia, 2001). The supply of flax oil containing high levels of LNA resulted in an increased accumulation of n-3 PUFA in the fat of TM also in experiments performed by Chanmugam et al (1992); their increased accumulation in BM was reported by Romboli et al (2002) and in both BM and TM by Olomu and Baracos (1991), Crespo and Esteve-Garcia (2001), Nguyen et al (2003), Dublecz et al (2004) and Valavan et al (2006).…”
Section: Resultsmentioning
confidence: 78%
“…The feeding of linseed oil rich in n-3 PUFA can be an effective method how to increase the tissue levels of these FA in broiler chickens (Olomu and Baracos, 1991;Chanmugam et al, 1992;Crespo and Esteve-Garcia, 2001;Lopez-Ferrer et al, 2001;Romboli et al, 2002;Nguyen et al, 2003;Dublecz et al, 2004;Valavan et al, 2006).…”
mentioning
confidence: 99%
“…On the other hand, both total n-6 fatty acids and the relation of n-6:n-3 were higher in the abdominal fat of birds fed with rations containing higher quantities of poultry fat. Chanmugam et al (1992) also demonstrated that the content of ω-3 fatty acids in the thigh of broilers might be increased by the addition of linseed oil or fish oil in the diet (Menhaden). Therefore, it has been suggested the inclusion of low dietary levels of fish oil together with another source of linoleic fatty acid to obtain an acceptable product with increased ratio between ω-3:ω-6 fatty acids.…”
Section: Fish Oilmentioning
confidence: 99%